Numerical modeling of transformation of nonlinear surface gravity waves under conditions of gulfs - Abbasov, Iftikhar Balakishievich (Computational Continuum Mechanics, 2012)
This paper is concerned with the numerical modeling of transformation of nonlinear surface gravity waves under conditions of a shallow gulf. A discrete model is constructed using nonlinear shallow water equations. Boundary and initial conditions are given. A system consisting of three equations is obtained by means of the splitting method with respect to physical processes. The approximation order is defined, and stability conditions for discrete models are examined. The system of equations is solved by the sweep method. The profiles of surface gravity waves obtained at various stages of their propagation are presented.
Keywords: shallow water equations; numerical modeling; nonlinear surface gravity waves; profile transformation